2017
DOI: 10.18203/2320-6012.ijrms20170137
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance pattern among aerobic bacterial isolates from osteomyelitis cases attending a Tertiary care hospital of North India with special reference to ESBL, AmpC, MBL and MRSA production

Abstract: Background: Osteomyelitis is a common cause of morbidity in developing countries. Its treatment comprises of surgical debridement of all necrotic bone and soft tissue along with use of appropriate antimicrobial therapy. Treatment is becoming increasingly troublesome due to rise in drug resistant isolates in osteomyelitis cases. The present study was done to determine the antibiotic resistance pattern among aerobic bacterial isolates from osteomyelitis cases.Methods: 125 samples from osteomyelitis cases were ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
7
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 13 publications
19
7
2
Order By: Relevance
“…This high predominance of the male gender and the youthful age group could be attributable to the greater likelihood of trauma and compound fractures in this population group in relation with their daily activities. These results are similar to those obtained in a study done in India in 2017 also reported a higher cases of osteomyelitis among younger age groups of 31-40 (32.8%) followed by 21-30 (25.6%) [4] . A study in Brazil, 2012 reported similar results [5] .…”
Section: Clinical Profilesupporting
confidence: 92%
See 3 more Smart Citations
“…This high predominance of the male gender and the youthful age group could be attributable to the greater likelihood of trauma and compound fractures in this population group in relation with their daily activities. These results are similar to those obtained in a study done in India in 2017 also reported a higher cases of osteomyelitis among younger age groups of 31-40 (32.8%) followed by 21-30 (25.6%) [4] . A study in Brazil, 2012 reported similar results [5] .…”
Section: Clinical Profilesupporting
confidence: 92%
“…The difference could be explained by the fact that they mostly had community acquired germs. The studies carried in India in 2013 [11] and 2017 [4] had comparable results with ours. They showed reduced sensitivity (less than 50%) to quinolones, aminoglycosides, Cotrimoxazole and to Cephalosporins.…”
Section: Sensitivity Testingsupporting
confidence: 87%
See 2 more Smart Citations
“…In the current study, the most common predisposing factor leading to osteomyelitis was trauma due to road side accidents accounting for 45% cases followed by post-operative infections (21%), orthopaedic implants (17%), haematogenous (11%), diabetes mellitus (4%) and others. This is in concordance with a study by Wadekar MD et al [11] who concluded trauma (44%) as the commonest predisposing factor followed by post-operative infections (23%) and orthopaedic implants (23%) and also similar to the findings of Khatoon R et al [12] according to whom the most common predisposing factor was trauma leading to open fractures (45.6%) In the present study, it was found that tibia was the commonest bone affected by the osteomyelitis (36%), followed by femur (32%). However, our study differs from study of Wadekar MD et al [11] which showed highest incidence of osteomyelitis in femur (48%) followed by tibia (23%).…”
Section: Discussionsupporting
confidence: 93%